The effect of training and knowledge management process towards organizational effectiveness - Voo, Yee Shee (2014)
The aim of this study to examine the relationship between training and knowledge management process towards organizational effectiveness. There is a total of 217 respondents participated in this study. The objectives of study were achieved after examining the relationship between individual / managerial skills training, process development skills training and knowledge management process (independent variable) by using different dimensions on organizational effectiveness (dependent variable). The findings shows that training is only partially contributing to the organizational effectiveness among the organizations in Tawau area where respondents of this study are working at. Process development skills training able to show significant relationship but not the individual / managerial skills training from data analysis. Knowledge management process also partially contributing to organizational effectiveness with knowledge acquisition, knowledge conversion and knowledge application showing significant relationships. Some of the items in this study are having relatively low and poor reliability, however the findings still can be used as a basic level of understanding of the effect of training and knowledge management process towards organizational effectiveness for relevant organizations in Tawau area. The findings of this study also can be used as a solid base for future researches.